2014
DOI: 10.1534/genetics.114.165647
|View full text |Cite
|
Sign up to set email alerts
|

The Set1/COMPASS Histone H3 Methyltransferase Helps Regulate Mitosis With the CDK1 and NIMA Mitotic Kinases in Aspergillus nidulans

Abstract: Mitosis is promoted and regulated by reversible protein phosphorylation catalyzed by the essential NIMA and CDK1 kinases in the model filamentous fungus Aspergillus nidulans. Protein methylation mediated by the Set1/COMPASS methyltransferase complex has also been shown to regulate mitosis in budding yeast with the Aurora mitotic kinase. We uncover a genetic interaction between An-swd1, which encodes a subunit of the Set1 protein methyltransferase complex, with NIMA as partial inactivation of nimA is poorly tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…C). Contrary to S. cerevisae and A. nidulans (Fingerman et al ., ; Govindaraghavan et al ., ), but in agreement with F. graminearum (Liu et al ., ), a faint band was still detectable for H3K4me1. However, it remains unclear at this moment whether there are indeed residual monomethylation levels in Δ set1 or whether this band is due to insufficient antibody specificity.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…C). Contrary to S. cerevisae and A. nidulans (Fingerman et al ., ; Govindaraghavan et al ., ), but in agreement with F. graminearum (Liu et al ., ), a faint band was still detectable for H3K4me1. However, it remains unclear at this moment whether there are indeed residual monomethylation levels in Δ set1 or whether this band is due to insufficient antibody specificity.…”
Section: Resultsmentioning
confidence: 78%
“…Identification of the H3K4 methyltransferase Set1 and demethylase Kdm5 in F. fujikuroi After analyzing the COMPASS component Ccl1 in F. fujikuroi (Studt et al, 2017), we have now identified the putative methyltransferase of this complex by determining the ortholog using QuartetS . The predicted protein FFUJ_02475 is the ortholog of the wellcharacterized H3K4-specific methyltransferases Set1 in S. cerevisiae and SetA in A. nidulans (Briggs et al, 2001;Govindaraghavan et al, 2014). FFUJ_02475 contains the catalytically active SET (IPR001214), N-SET (IPR024657) and Post-SET (IPR003616) domains as well as an RNA-binding (IPR035979) domain also present in Set1 and SetA from S. cerevisiae and A. nidulans, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Neurospora crassa Set1 is not essential and has been shown to regulate the circadian rhythm (Raduwan et al, 2013). Also in A. nidulans set1 Δ alone is viable but synthetic lethal with regulators of mitosis which provides a link between H3K4 methylation and H3S10 phosphorylation (Govindaraghavan et al, 2014). Cells of the rice pathogen M. oryzae lacking MoSet1 cannot develop proper infection and asexual reproduction structures (Pham et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…immunoprecipitation approach, using antibodies against a variety of modified histones, may be required to reveal the biochemical nature of snxA defects. Of interest in this regard is the recent finding of a functional relationship between the Set1/ COMPASS complex (Set1c), an H3K4 methyltransferase, and both the CDK1 and NIMA mitotic kinases, in which Set1c and the two kinases are required for mitotic induction and progression (Govindaraghavan et al 2014). In general, H3K4 di-and trimethylation by Set1c has been associated with gene activation in euchromatin, and in humans has been suggested to "bookmark" active genes so that they can resume transcription following exit from mitosis (Blobel et al 2009;Kelly et al 2010).…”
Section: Discussionmentioning
confidence: 99%